Sosialisasi Pentingnya Mengasah Kemampuan Berpikir Kritis Bagi Guru Matematika di Era VUCA - Astri Wahyuni Astri; zetriuslita zetriuslita; Suripah Suripah; Leo Adhar Effendi Leo; Sindi Amelia Sindi; Agus Dahlia Dahlia; Endang Istikomah Iis; Rezi Ariawan Rezi (Community Education Engagement Journal, 2020)
The ability to think critically is very important for mathematics teachers. Therefore, this service activity aims to provide participants with an understanding of the importance of honing critical thinking skills for mathematics teachers. This service was carried out on Tuesday June, 30 2020 and was carried out through the application Zoom Meeting and live YouTube Mathematics Education FKIP UIR. The method used in the implementation of this community service activity is the percentage method to convey material, the question and answer method and the discussion method. The instrument used was a percentage of service material slides. The results of this service activity can be said to be quite good. This can be seen from the responses of teachers who begin to understand the importance of critical thinking skills. This service activity has the benefit of making the teacher more eager to hone their critical thinking skills so that they can do better and be useful for students.